Spot Urine Sodium and Potassium Ratio as a Predictor of Acute Kidney Injury and Survival in Decompensated Cirrhosis - Bhuyan, Sambit Kumar; Karunakaran, Premkumar; K., Muthukumaran; A., Aravind; Selvi, Caroline; R., Murali; A., Chezhian; I., Shubha (International Journal of Innovative Research in Medical Science, 2022)
Background: Acute kidney injury (AKI) is associated with high mortality in decompensated cirrhosis, so early prediction is vital. Urinary sodium excretion may have an association with mortality in decompensated cirrhosis. The study aims to investigate the spot urinary Na+/K+ ratio & fractional excretion of sodium in patients admitted with decompensated cirrhosis and evaluate its relationship with AKI and short-term survival. Method: It was a prospective analysis of 200 patients with decompensated cirrhosis over 6 months. Urinary sodium excretion was analyzed by spot urine Na+/K+ ratio & FENa. Receiver operator curve (ROC) analysis was done to find cut-off values of Na+/K+ in predicting AKI at admission, during the hospital stay, and survival probability. P-value <0.05 was considered significant. Result: AKI of admission was observed in 36.5% of patients and associated with low urine Na+/K+ and low urine Na+. 24.5% of patients who had no AKI at admission progressed to AKI during the hospital stay and were associated with low spot urine Na+/K+ and low FENa+. Area under curve (AUC) for urinary Na+/K+ (cutoff, sensitivity/specificity) at admission was 68.6% (≤1.36, 75.5/59.1), during hospital stay was 73.4% (≤ 1.64,77.6/67.5) and of short-term mortality was 73.4% (≤ 1.34, 93.3% /58.8). Conclusion: Spot urine Na+/K+ ratio at admission is a simple, predictable tool to predict AKI during the hospital stay and 30 days mortality in decompensated cirrhosis.